2019
DOI: 10.1155/2019/3586370
|View full text |Cite
|
Sign up to set email alerts
|

The Needs for Visual Improvement of Patients Presented at Low-Vision Center in Wenzhou, China

Abstract: Purpose. To characterize the needs for visual improvement of new-visit patients with low vision.Methods. This cross-sectional study collected detailed information of patients presented at low-vision center of the Eye Hospital of Wenzhou Medical University between January 2015 and January 2017. A questionnaire interview, including demographic information and needs for visual improvement, was conducted before ophthalmology examinations.Results. The main need for visual improvement was engagement in hobbies (68.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
1
0
2
Order By: Relevance
“…Paying attention to these findings raises the need to provide rehabilitation services to these patients. In the study of Li et al, patients' rehabilitation in performing activities was one of the needs of people with low vision [22]. Findings of other studies have also shown the positive effects of rehabilitation services on improving the quality of life and physical ability of people with low vision [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Paying attention to these findings raises the need to provide rehabilitation services to these patients. In the study of Li et al, patients' rehabilitation in performing activities was one of the needs of people with low vision [22]. Findings of other studies have also shown the positive effects of rehabilitation services on improving the quality of life and physical ability of people with low vision [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…deficiência visual nas ocupações e atividades significativas para seu cotidiano e a participação social. A maquiagem é citada como demanda de intervenção de serviços que prestam atendimento especializado a pessoas com deficiência visual (CORRÊA; SANTANA, 2014;LI et al, 2019) e emergiu como demanda relevante pelas adolescentes e mulheres atendidas pelo projeto.…”
unclassified
“…O desempenho independente e/ou autônomo nas atividades de vida diária, dentre elas a maquiagem, constitui-se como demanda identificada pelas pessoas com deficiência visual deste e de outros estudos (CORRÊA;SANTANA, 2014;LI et al, 2019) e importante foco de estudo e intervenção da Terapia Ocupacional. As intervenções no desempenho dessas atividades devem sempre ser condizentes com as potencialidades de cada pessoa com deficiência visual e de acordo com as atividades de O uso da apostila foi considerado como outra forma de auxílio.…”
unclassified